PERANAN KREDIT USAHA PEMBERDAYAAN MASYARAKAT DALAM MENINGKATKAN PENDAPATAN PETANI KENTANG DI KECAMATAN KAYU ARO : Studi Kasus Kelompok Tani Mekar Sejati Desa Sungai Rumpun - Masrida Zasriati (Institut Agama Islam Negeri Kerinci, 2021)
ABSTRACT Purpose: The research objectives to be achieved in this research are to determine farmers' income before giving KUPEM, knowing farmers' income after giving KUPEM, knowing KUPEM on increasing farmers' income. Design/Methodology/Approach: This research is a quantitative and qualitative descriptive study. Quantitative analysis was carried out by simple linear regression analysis to determine the effect of the independent variable on the dependent variable. Findings: The results of this study indicate that there is a positive and significant effect between KUPEM and farmers' opinions, where farmers' income has increased after KUPEM was given. Research implications: From the results of this study it is known that in order to increase farmers' income, the government must continuously provide business credit to empower farmers in increasing their income.